Can AI Improve Newborn Genetic Screening? - Rasit Dinc (Rasit Dinc Digital Health & AI Research, 2021)
Newborn screening is a critical public health program that identifies infants with rare but serious genetic, metabolic, and hormonal conditions. Early detect...
Keywords: Precision Medicine and Genomics; Improve; Newborn; Genetic; Artificial Intelligence; Machine Learning; Precision Medicine